AN EXPLANATION ON THE IDEOLOGICAL DEVIATION OF ECONOMIC LEGISLATURE IN INDONESIA - Aurora Jillena Meilala; Dian Khoreanita; Citraresmi Widoretno Putri; Jonathan Andre Woods (Bajang Institute, 2022)
This article is aimed to narrate the transformation of the Indonesian economic system as stipulated under its legislation. The methods of the paper’s research being Conceptual, Philosophical, and Analytical which are used to discover and expound any relevant findings. The focus of the article is the Indonesian authentic “third way” which was introduced long before Giddens sparked his idea. It was Ekonomi Kerakyatan (people-centred Economy) that had been introduced and widely discussed before independence at the meetings of the Investigating Committee for Independence Preparatory Work (BPUPKI). Claimed as the authentic Indonesian socialism, it was rooted in the value of Pancasila as Indonesia’s Weltanschauung (Philosophische- Grondslag). Ekonomi Kerakyatan was introduced with the main characters of cooperativism and kinship. The aim of this paper is ultimately to explore the idea of Ekonomi Kerakyatan in its original perspective of Indonesia’s founding fathers. The first part of the paper will explain how Ekonomi Rakyat was defined and postulated under the Indonesian Constitution. The second part will explain the transformation of the economic legislature, how it happened and its implication to national development. And the last part will explain the prescriptive resolution to reinvigorate Ekonomi Kerakyatan as the main character of Economic Democracy in Indonesian Legal Framework. Ultimately, this paper also aimed to link the correlation between law, economics and politics. In the end, it can be concluded that the economic system should be narrated in a sound legal framework, while the process of legal drafting and legal enforcement depends on its political commitment.